Analysis of Students' Higher Order Thinking Skills in Solving Open-Ended Problems on the Topic of the System of Linear Equations in Two Variables - Ningsih, Febria; Pitri, Dela Mike; Putri, Rahmi (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study aims to describe how students' Higher Order Thinking Skill (HOTS) ability is reflected in solving open-ended problems related to the topic of system of linear equations of two variables. This type of research is descriptive with a qualitative approach aimed at uncovering the description of students' HOTS ability in answering open-ended problems related to the topic. Three students from three different groups, namely high, medium and low performers, were involved in this study. The results showed that students with high HOTS ability were able to solve open-ended problems at the cognitive level involving analysis, evaluation, and solution creation. Students with moderate HOTS ability were only able to solve problems at the analysis and evaluation levels, without reaching the solution creation level. Meanwhile, students with low HOTS ability were only able to solve problems at the analysis level, without reaching the evaluation and solution creation levels